Spending too much operational costs are still become mainly problem in bisnis organization include PT DEF which move in Frozen Shrimp production. This is important for performing prevention act and reaction act to decrease this waste costs . The prevention act can be doing by performing HACCP (Hazard Analysis and Critical Control Point) In production process. Reaction act can be done by performing SPC (Statistical Process Control) analyze methode. Before performing HACCP, the bisnis units are mu - Iis Diatin; Narni Farmayanti; Zaky Eka Lesmana (Buletin Ekonomi Perikanan, 2006)
Spending too much operational costs are still become mainly problem in bisnis organization include PT DEF which move in Frozen Shrimp production. This is important for performing prevention act and reaction act to decrease this waste costs . The prevention act can be doing by performing HACCP (Hazard Analysis and Critical Control Point) In production process. Reaction act can be done by performing SPC (Statistical Process Control) analyze methode. Before performing HACCP, the bisnis units are must be complied by pre-requisite programs which is SSOP (Standard Sanitation Operating Procedure) and GMP (Good Manufacturing Peractices). SPC analyze performed by problem identification, Pareto Diagram, Fishbone Diagram, and Control Chart Diagram. Calculating waste costs production performed after performing HACCP and performing SPC. The result of the study showed that HACCP at PT DEF has B level. Also error indicate in packing and labeling. Total loss of error is Rp. 12500 and loss of time was 75 minutes In 171 prodUction turnover.